ADDRESSING THE GOALS OF SUSTAINABLE DEVELOPMENT IN THE ARAB PRESS:: (An analytical study in the newspapers (Al-Sabah Iraqi newspaper, Algerian ech-chaab Newspaper, and UAE Al-Ittihad Newspaper) (A Research Drawn from Master Thesis) - Mahdi, Raghda Salah; Ghntab, Azhar Sabeeh (ALBAHITH ALALAMI, 2020)
The problem of this research is: What are the sustainable development goals that received the priority in the press addressing of the newspapers under study? What are the journalistic arts adopted by these newspapers in addressing the sustainable development goals? What are the journalistic sources that Arab newspapers depended on when addressing the sustainable development goals? What are the geographic range the Arab newspapers adopted in addressing the sustainable development goals? The research is categorized into descriptive research, adopting the survey method, and using the content analysis method. The sample of research was determined by the preparation of the Arabic newspapers (Al-Sabah Iraqi newspaper, Algerian ech-chaab Newspaper, and UAE Al-Ittihad Newspaper) issued from January 1 to June 30, 2018, and extracted according to the system of regular random sample. The research tools were (Content Analysis Form). The research reached the following conclusions: The sustainable development goal: the eleventh "sustainable local cities and settlements" and the eighth goal "economic growth and decent work" and the sixteenth goal "peace, justice and institutions" won the priority of press treatment in the Arab newspapers in question. These goals occupied the first three ranks consecutively, after having an acceptable treatment ratio compared to other targets. Most of the SDGs were addressed by the report’s technician and journalist, which is consistent with the data and results of previous scientific research, according to which the treatment of issues related to sustainable development is often done through news arts. The Arab newspapers in question obtained most of their information dealing with the sustainable development goals from their own sources, followed by academics and researchers, and the anonymous sources recorded a clear presence. This indicates the diversification in the sources’ dependence, despite the apparent occupational deficiency of the unknown sources. Addressing the SDGs on the basis of geographical scope showed that the highest percentage of journalistic issues addressed were within the local, then international, and finally Arab domain.